Applying Generative Artificial Intelligence (Generative AI) to Enhance Public Sector Management Efficiency: Opportunities, Challenges, and Governance Approaches Under Digital Governance: Applying Generative Artificial Intelligence (Generative AI) to Enhance Public Sector Management Efficiency: Opportunities, Challenges, and Governance Approaches Under Digital Governance - Yangay, Vansawaang; Upanisakorn, Natnalin; Phuyiachit, Narong; Ubpanisakorn, Wiphaphun (RATANABUTH JOURNAL, 2026)
Generative Artificial Intelligence (Generative AI) has emerged as a vital element in the transformation of public administration in the digital era. This technology has the capacity to augment operational efficiency, elevate the quality of public services, and facilitate data-driven policy formulation. This scholarly study seeks to evaluate the function and prospects of Generative AI in public administration, investigate the opportunities and obstacles associated with its implementation, and recommend governance frameworks based on the tenets of digital governance. The study utilizes a documentary analysis of research, scholarly papers, reports from international organizations, and pertinent documents at both national and international levels. The results demonstrate that Generative AI may enhance public sector operations in multiple aspects, such as the creation of intelligent public service systems, increased efficiency in government data administration, minimization of paperwork, and advancement of knowledge management within organizations. Nonetheless, its execution encounters considerable constraints and hazards, encompassing data precision, privacy, personal data safeguarding, cybersecurity, transparency in system decision-making, and ethical implications of AI utilization. Consequently, the government must formulate suitable policy frameworks and regulatory mechanisms, alongside enhancing digital competencies among personnel, instituting standards for responsible AI utilization, and fostering sectoral engagement to guarantee the effective, transparent, and ethical application of AI. This will enhance the quality of public administration and promote sustainable national growth in the future.